2023
DOI: 10.1038/s41598-022-26637-6
|View full text |Cite|
|
Sign up to set email alerts
|

IL-4Rα signalling in B cells and T cells play differential roles in acute and chronic atopic dermatitis

Abstract: Atopic dermatitis (AD) is a common pruritic inflammatory skin disease with complex environmental and genetic predisposing factors. Primary skin barrier dysfunction and aberrant T helper 2 (TH2) responses to common allergens, together with increased serum IgE antibodies, characterise the disease. B and T cells are essential in the disease manifestation, however, the exact mechanism of how these cells is involved is unclear. Targeting interleukin 4 receptor alpha (IL-4Rα), an IL-4/IL-13 signalling axis, with dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The IL-22 serum levels correlated much better with the clinical improvement of the Dupilumab-treated patients. Several studies reported similar results, suggesting that IL-22 might be a potential reliable biomarker [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 69%
“…The IL-22 serum levels correlated much better with the clinical improvement of the Dupilumab-treated patients. Several studies reported similar results, suggesting that IL-22 might be a potential reliable biomarker [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the present study evaluated the expression levels of CD11b, which is commonly used as a biomarker for NK cells, monocytes, dendritic cells and neutrophils (77)(78)(79)(80). B cells and T cells are also important classes of immune cells that serve an important role in skin inflammation and skin cancer progression (81,82). In future studies, the relationship between T cells and B cells and the progression of skin cancer should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, Th2 cells primarily secrete IL-4 and IL-5, which stimulate B cells to produce IgE, in uencing the levels of IgG1 and IgG2a, as well as the production of various in ammatory cytokines [35]. IgE levels also play a role in sensitizing allergens [36,37].…”
Section: Discussionmentioning
confidence: 99%